2014
DOI: 10.1093/beheco/aru169
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variability in habitat use: evidence for a risk management syndrome in roe deer?

Abstract: The way an individual reacts to the risk of predation or disturbance may have important consequences for its immediate and future survival. Risk is likely perceived differently by individuals in relation to among-individual differences in correlated behavioral traits, that is, syndromes or personalities. Given that animals can avoid the risk of predation/disturbance through modification of their habitat use, we might expect individuals of differing behavioral types to adopt contrasting tactics of habitat use w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 64 publications
(71 reference statements)
4
71
1
Order By: Relevance
“…Whereas the deer's use of more open forests does not necessarily mean they are more likely to be shot in a forest, it does mean they are more likely to be shot in general (indeed most individuals were shot on agricultural pasture in our study). This dynamic spatial response to the onset of hunting could correlate with other risk management behaviours such as increased vigilance (Bonnot et al, 2014) or the tendency to hide rather than run when encountering humans (Ciuti et al, 2012). In contrast to our study, Ciuti et al (2012) found that individual differences in behaviour existed before the hunting season started, and highlighted that this reflected personality traits.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Whereas the deer's use of more open forests does not necessarily mean they are more likely to be shot in a forest, it does mean they are more likely to be shot in general (indeed most individuals were shot on agricultural pasture in our study). This dynamic spatial response to the onset of hunting could correlate with other risk management behaviours such as increased vigilance (Bonnot et al, 2014) or the tendency to hide rather than run when encountering humans (Ciuti et al, 2012). In contrast to our study, Ciuti et al (2012) found that individual differences in behaviour existed before the hunting season started, and highlighted that this reflected personality traits.…”
Section: Discussioncontrasting
confidence: 85%
“…A typical situation for large grazing mammals is that individuals have to choose between open habitats with good foraging opportunities, but where they are visible to predators, and habitats that provide more cover from potential dangers but which might limit foraging efficiency (Godvik et al, 2009;Werner, Gilliam, Hall, & Mittelbach, 1983). Individuals can differ substantially in how they respond to such a trade-off (Bonnot et al, 2014). The shyebold continuum is one of the most studied personality axes in animals and characterizes inherent tendencies in how an individual responds to novelty, innovation and risk taking (Quinn & Cresswell, 2005;Wolf & Weissing, 2012).…”
mentioning
confidence: 99%
“…Individual characteristics in terms of their behavioural phenotype (i.e. animal personality) may influence juvenile survival, natal dispersal and the resource acquisition-risk avoidance trade-off (Bonnot et al 2015). Because these individual differences have important repercussions for population dynamics, they also have potential knock-on effects on population management.…”
Section: Population Dynamicsmentioning
confidence: 99%
“…This adds to the limited (but rapidly growing) evidence for the presence of consistent individual differences in FID in wild vertebrate populations (see, e.g., Carrete and Tella 2010;Carter et al 2010;Evans et al 2010;Seltmann et al 2012;Petelle et al 2013;Bonnot et al 2015), and highlights the potential of FID as a candidate trait for future research on the ecology and evolution of differences in behaviour in Sable Island horses. Although FID is typically considered in the context of predator-prey interactions and human-wildlife disturbance, research in wild vertebrates, including the present study, indicate that it may find wider applications as a way to quantify consistent individual differences in risk aversion or boldness.…”
Section: Discussionmentioning
confidence: 82%
“…However, as the costs and benefits of leaving also depend on an individual's state (e.g., sex, body condition, social status), persistent differences in FID among individuals are also expected. Although few studies have estimated the repeatability of FID, consistent among-individual differences have been documented, for example, in Burrowing Owls (Athene cunicularia (Molina, 1782)) (Carrete and Tella 2010), Namib Rock Agamas (Agama planiceps Peters, 1862) (Carter et al 2010), yellowbellied marmots (Marmota flaviventris (Audubon and Bachman, 1841)) (Petelle et al 2013), and roe deer (Capreolus capreolus (L., 1758)) (Bonnot et al 2015). Among-individual variation in FID has also been shown to have a genetic basis and to be related to life-history differences (Møller 2014;Carrete et al 2016).…”
Section: Introductionmentioning
confidence: 98%